USING OF VISUALIZATION ELEMENTS IN HIGHER EDUCATION INSTITUTIONS WITH SPECIFIC LEARNING ENVIRONMENT - Pedorych, A. V. (НАУКОВІ ЗАПИСКИ, 2019)
In this article are considered solutions for problems related to the need of improving the quality of explaining educational information while simultaneously increasing of training information for cadets and students of higher educational institutions with specific learning environment. The didactic and methodical features of multimedia using within the training of cadets are revealed. The experience of using multimedia and presentations in the educational process is presented. The advantages and disadvantages of visualization of educational material for higher education graduates of educational institutions with specific learning environment are studied. The potential of using these learning technologies with increasing of proportion of independent material studying is revealed.